Importance of Internal Audit Capability in Management Accounting and Organization Performance - Hasnah, Haron; Ishak, Ismail; Nur Ain Zakiah, Mohd Yusof (2016)
The purpose of this paper is to explain the importance of internal audit capability in enhancing the management accounting and performance of Malaysian public sector organizations. The structure of public sector organization in Malaysia comprises of several level and types of organizations which lead to the complexity of the structure. Therefore, it requires a comprehensive procedure and guidelines especially in financial management. This study specifically focused on the role of internal audit in two different types of public sector entities i.e., state level and state statutory body. An explanatory case study method was used to collect the data whereby semi structured interviews, informal conversations, questionnaire and document reviews were conducted. It is found that internal audit unit in PSA obtained higher capability level of Level 2 (infrastructure) with overall percentage capability of 57%. CSA scored level 5 (optimized) for four of the IACM dimensions which are Professional Practices, Performance Management and Accountability, Organizational Relationships and Culture, as well as Governance Structure. CSB only achieves level 5 (optimized) for dimension of performance management and accountability. For dimension of governance structure, CSB achieves level 3 (integrated). Other three dimensions of services and role of internal audit, professional practices and organizational relationships and culture achieves level 2 (infrastructure). However, CSB scores poorly for people management dimension which is only level 1 (initial) which resulting the overall capability of only level 1 (initial) with overall percentage of 52%. There is a critical need to review the dimensions of services and role of internal audit, people management, and professional practices for both organizations to enhance the effectiveness of the IA function. Implications and suggestions for further studies are also provided.